Pendugaan Cadangan Karbon Above Ground Biomass (AGB) pada Tegakan Agroforestri di Kabupaten Langkat (The Estimate of Carbon Stocks Above Ground Biomass (AGB) on Agroforestry Stands in Langkat) - Yusrani Dwi Paulina Malau; Rahmawaty Rahmawaty; Riswan Riswan (Program studi Kehutanan USU, 2013)
Agroforestry system is estimate to have a high potential for carbon sequestration in the atmosphere. Agroforestry systems contributed to reducing the increase in atmospheric CO2 and other green house gases by increasing carbon in the soil and reduce the pressure for forest clearing where the carbon comes from CO2 is taken up by plants and stored in the form of biomass. This study aimed to quantify the carbon content. Calculation of carbon stocks was done with non-destructive by using allometric method. The results indicated that the types of vegetation in agroforestry in Langkat was are sengon, mindi, sungkai, coklat, mangga, mahoni, nangka, durian, karet, kemiri, jati, jengkol, petai, and duku. The amount of carbon stocks in agroforestry stands in Sei Bingai sub-district, Bahorok sub-district, and Wampu sub-district was 58,438 ton/ha, 63,005 ton/ha, and 56,76 ton/ha. Differences in carbon content acquisition was influenced by vegetation density, diversity of size, and distribution of vegetation density. Keywords: Agroforestry, Carbon Stock, Above Ground Biomass